(untitled) (Historia, 2021)
The debate on the political and constitutional position of the non-whites in the Orange River Colony, 1900-1910 The debate on the non-whites’ political and constitutional position after the Anglo- Boer War was important because race relations attracted so much attention in an outside the Orange River Colony. It served as a precursor for the development of the non-white question. The non white franchise question was the main issue in white and non-white political circles. The question made its first appearance in the Memorandum of Sir Joseph Chamberlain (Minister for the Colonies) in January 1900. This memorandum extended the franchise to all British subjects in the Colony, thus not only to English and Afrikaans-speaking subjects, but also to those non-whites who had western standards of civilization and lived accordingly. The proclamation whereby the Orange River Colony was annexed, did not take the place of the old republican law which barred the non-whites from civic rights. This included voting rights on municipal level. Besides this, Article 8 of the Vereeniging Peace Treaty (1902), stipulated that the non-white franchise question was to be considered only after the granting of self-government to the Orange River Colony in 1907. Daar was in die jare 1900-1910 in die Oranjerivierkolonie heelwat bespreking en debat oor die politiek-grondwetlike posisie van die gekleurdes, swartes sowel as Kleurlinge, en wat die toekomstige beleid in hierdie verband behoort te wees. Die debat was belangrik omdat rasseverhoudinge in die jare baie aandag geniet het, binne en buite die kolonie, en was rigtinggewend vir die ontwikkeling van die gekleurde "vraagstuk". Die Anglo-Boereoorlog (1899-1902) was nog volstoom aan die gang toe Joseph Chamberlain, Minister van Kolonies, op 10 Januarie 1900 sy memorandum oor die koloniale beleid ten opsigte van gekleurdes en die toekomstige skikking van sake in die Brits-Suid- Afrikaanse kolonies die lig laat sien het. Die vraagstuk van die stemreg van gekleurdes in die Oranjerivierkolonie, is die eerste keer in die memorandum aangeroer. Beginsels geformuleer deur lord Salisbury, Britse premier en Konserwatiewe Partyleier, het sterk neerslag gevind in die memorandum. Hy het Afrikaans- en Engelssprekendes in die kolonie wat op 24 Mei 1900 geannekseer is, polities op gelyke voet geplaas en bepaal dat stemreg aan alle Britse onderdane in die kolonie verleen sou word. Gevolglik sou stemreg ook na die gekleurdes wat aan sekere beskawingsvereistes voldoen het, uitgebrei word. Dit sou op dieselfde wyse as in die Kaapkolonie geskied.